Self-Efficacy, Goal Orientation, and Relationship Ideologies Among Incarcerated Men and Their Romantic Partners - Tadros, Eman (Crime & delinquency, 2025)
Previous research has found that self-efficacy may be higher during incarceration, which may be a time when individuals reflect, leading incarcerated individuals to create lasting behavioral changes. Self-efficacy may be used to prepare for upcoming community reentry and improve other life outcomes while managing stress during and after incarceration. Utilizing a solution-focused brief therapy conceptualization and data from the Multi-Site Family Study of Incarceration, Parenting, and Partnering, we assess the relationship between self-efficacy, goal orientation, and romantic relationship ideologies with incarcerated men and their non-incarcerated partners. The results indicate that self-efficacy and goal orientation skills cultivated while incarcerated are strongly associated with overall relationship ideologies between the incarcerated male partner and his non-incarcerated partner. While these results substantiate the importance of romantic relationship building during time in prison, they speak to greater capabilities of incarcerated men to form other, non-romantic relationships with their children and family members upon release. Clinical implications and future directions are discussed.